Pengembangan Modul IPA Berkarakter Religi Islami untuk Meningkatkan Literasi Sains Materi Sistem Peredaran Darah pada Manusia di Sekolah Dasar - Irkham Irkham (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this development research was to describe the validity, practicality and effectiveness of the IPA module with Islamic religious characteristics to increase scientific literacy in the material of the human circulatory system in grade V elementary schools. This research is research and development by modifying the ADDIE model development stages carried out systemically and systematically. The stages start from Analysis (Analyzing), Design (Designing), Development (Developing), Implementation (Implementing), and Evaluation (Evaluating). However, in this study the stages of developing the ADDIE model were modified only to the Implementation (Implement) stage. The analysis phase includes the introduction or analysis of needs by analyzing the characteristics of students, the learning process, and the learning resources that are often used. The design phase includes initial product design such as test preparation, selection of learning media, format selection, initial design. The develop stage is to revise the module product development that has been produced in the initial design activities. At this stage revisions were also carried out based on input from experts and data obtained from the results of practical trials. The data collection instruments in this study were validity sheets for subject matter expert lecturers, media experts and practitioners, student readability sheets, practicality sheets for practitioners, lesson plans validation sheets, validation sheets for scientific literacy questions, pretest and posttest scientific literacy questions. This instrument was developed based on the advisory lecturer's defense, the assessment of expert lecturers, practitioners, and limited trials on students and practitioners. The stage of implementing the module developed in class V students at SDN Ketanggan 03 Gringsing District. The Implementation Stage is the stage of using modules that have been developed on a wider scale, through the website address of the IPA Module with Islamic Religious Character which has been online so that it has been spread via Google and can be accessed in a browser. The data analysis technique used was the n-gain test and the T-test. The Ngain test value in this study was obtained 0.32 with the moderate improvement category, and the T-test value was obtained Sig. 0.033 <0.05 means that there is an effect of using the Science module with Islamic religious characteristics to improve students' scientific literacy skills. The results showed that the science module with Islamic religious character that was developed proved to be valid, practical, and effective so that it was very suitable for use in learning science in elementary schools to improve students' scientific literacy skills. Keywords: Science module, Islamic religious character, scientific literacy ability